2020
DOI: 10.1037/bul0000298
|View full text |Cite
|
Sign up to set email alerts
|

Rewards of kindness? A meta-analysis of the link between prosociality and well-being.

Abstract: In recent decades, numerous studies have suggested a positive relationship between prosociality and well-being. What remains less clear are (a) what the magnitude of this relationship is, and (b) what the moderators that influence it are. To address these questions, we conducted a meta-analysis to examine the strength of the prosociality to well-being link under different operationalizations, and how a set of theoretical, demographic, and methodological variables moderate the link. While the results revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
158
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 219 publications
12
158
1
Order By: Relevance
“…In the last several decades, this simple maxim has been placed under scientific scrutiny and accumulated a sizable body of evidence that attests to its veracity. Two recent meta-analyses found that prosocial activities produce a small positive effect on "emotional well-being"-a catch-all term that includes happiness, eudaimonic well-being, positive affect, psychological flourishing, and the absence of negative emotions [20,24]. Prosocial effects have been observed among children as well as adults and in samples across the world [20,[25][26][27][28][29][30].…”
Section: Prosocial Behavior's Effects On Emotional Well-being and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last several decades, this simple maxim has been placed under scientific scrutiny and accumulated a sizable body of evidence that attests to its veracity. Two recent meta-analyses found that prosocial activities produce a small positive effect on "emotional well-being"-a catch-all term that includes happiness, eudaimonic well-being, positive affect, psychological flourishing, and the absence of negative emotions [20,24]. Prosocial effects have been observed among children as well as adults and in samples across the world [20,[25][26][27][28][29][30].…”
Section: Prosocial Behavior's Effects On Emotional Well-being and Mental Healthmentioning
confidence: 99%
“…Thus, while the available evidence suggests that prosocial behavior positively influences emotional well-being and improves mental health, it is likely that reported effect sizes are too large. In fact, a recent high-powered replication of prosocial spending research found that effects across three studies ranged from non-existent to modest [24,43]. Similarly, a recent meta-analysis of positive psychology interventions found that effect sizes were substantially overestimated due to an overreliance on small-N studies [22].…”
Section: Prosocial Behavior's Effects On Emotional Well-being and Mental Healthmentioning
confidence: 99%
“…Finally, prosociality has been a consistent source of meaning in life (Van Tongeren et al, 2016b). Not only does prosociality help reduce existential anxiety in the light of reminders of one's frailty (Jonas et al, 2002), but a recent meta-analysis confirms that it also contributes to well-being and flourishing life (Hui et al, 2020). In fact, experimental work has demonstrated the focusing on others, compared to focusing on oneself, enhances psychological flourishing (Nelson et al, 2016), providing additional evidence for the transformative nature of prosociality.…”
Section: Toward Flourishingmentioning
confidence: 99%
“…For them, the way they look at their career is as something pleasant, satisfying, and socially beneficial (Khan et al, 2020). As reported by Hui et al (2020), it is easy to identify the WB or happiness of an individual from a subjective perspective. Nevertheless, as suggested by some researchers, it is better to use a rigorous approach.…”
Section: Individual Well-beingmentioning
confidence: 99%
“…Nevertheless, as suggested by some researchers, it is better to use a rigorous approach. This would prove a more complex task (Hui et al, 2020). According to academicians, there are two old philosophical orientations.…”
Section: Individual Well-beingmentioning
confidence: 99%